PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS PUZZLE PADA MATA PELAJARAN PPKn MATERI HAK DAN KEWAJIBAN UNTUK SISWA SEKOLAH DASAR KELAS IV SDN SAMBIREJO 1 - Lia Tri Utami; Frans Aditia Wiguna; Kukuh Andri Aka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive puzzle-based multimedia on PPKn subjects with Rights and Obligations material for fourth grade students of SDN Sambirejo 1. The method used is Research and Development (R&D) with the ADDIE development model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were fourth grade students. Validation was carried out by material experts and media experts, then followed by limited trials (9 students) and extensive trials (18 students). The validation results showed that the product was very feasible to use. The trial results showed the effectiveness of the media with classical completeness reaching 100%. It can be concluded that this puzzle-based interactive multimedia is very valid, practical, and effective in supporting PPKn learning.